Ensino de ciências em canções regionais: alternativa didática para o processo educativo no ensino fundamental - Rodrigues, Rayane Delmondes Souza (2021)
The songs, besides being compositions that play with several human emotions, paint a reality of place, feelings, experiences, among other things the author wants to express, can be devices which to help the teaching and learning process. This study addresses issues related to the use of Amazonian songs in the science teaching process of science. The study aims to analyze in what terms regional Amazonian songs constitute didactic resources for science teaching and facilitate learning. The work was based on Bachelard (1996), Merleou-Ponty (1999), Heller (1985), Mello, Dallan and Grellet (2004), Moreira and Massarani (2006) and Manzani and Rosa (2012). In order to achieve the goals, it was adopted qualitative research, based on phenomenological foundations, following the steps: bibliographic research with the setting of concepts on Science teaching; survey, through the study of regulatory documents of the panorama of Science teaching in the city of Manaus and Brazil; state of art of published works about the relationship between music and science teaching; and selection of songs with potential for teaching natural sciences, which were heard and extracted content for the didactic sequence construction: first it should be made available to the student listen to the song and read the lyrics, followed by guidance to select words related to Sciences, whose records must be done via text production and mind maps. The second stage of the activity is the presentation of the content without associating it with the lyrics of the song. For this, the teacher should teach the class and ask students to register their perceptions again through texts and mental maps. Finally, the third stage proposes the association of the contents taught to the lyrics of the song and once again students will be invited to produce texts and mental maps to document their perceptions about that activity. The written records will allow the teacher to identify the stages of the student's learning process throughout the activity. The result of this research was the construction of a didactic-methodological proposal for the use and application of regional songs in the classroom and the development of a database of songs with potential to be used for science teaching with elementary school students. The state of Amazonas has a cultural richness that, among several aspects, can be highlighted by the songs composed by local artists that address issues of the regional context and, when observed from an educational perspective, can contribute significantly to the learning process. The countless authors of this region sing about nature, traditions, beliefs, and values of the Amazon. Thus, the use of regional songs allows not only to teach the content, but also enables enrichment and cultural appropriation for Amazonian students. Key-words: Amazonian songs; Didatic proposal; Science teaching